Dietary probiotic supplementation improves growth and the intestinal morphology of Nile tilapia. (12th January 2017) - Ramos, M. A.; Batista, S.; Pires, M. A.; Silva, A. P.; Pereira, L. F.; Saavedra, M. J.; Ozório, R. O. A.; Rema, P.
Abstract : Probiotic administration can be a nutritional strategy to improve the immune response and growth performance of fish. The current study aimed to evaluate the effects of a probiotic blend ( Bacillus sp., Pediococcus sp., Enterococcus sp., Lactobacillus sp.) as a dietary supplement on growth performance, feed utilization, innate immune and oxidative stress responses and intestinal morphology in juvenile Nile tilapia ( Oreochromis niloticus ). The probiotic was incorporated into a basal diet at three concentrations: 0 g/kg (A0 : control), 3 g/kg (A1 : 1.0×10 6 colony forming unit (CFU)/g) and 6 g/kg (A2 : 2.3×10 6 CFU/g diet). After 8 weeks of probiotic feeding, weight and specific growth rate where significantly higher in fish-fed A1 diet than in fish-fed A0 . Alternative complement in plasma was significantly enhanced in fish-fed A2 when compared with A0 . The hepatic antioxidant indicators were not affected by probiotic supplementation. Villi height and goblet cell counts increased significantly in the intestine of fish-fed A1 and A2 diets compared with A0 . The dietary probiotic supplementation was maintained until 20 weeks of feeding. Then the selected immune parameters, digestive enzymes and apparent digestibility of diets were studied. No effect of probiotic feeding was observed after that longer period supplementation. The dietary supplementation of mixed species probiotic may constitute a valuable nutritional approach towards a sustainable tilapia aquaculture. The improvement of the immune responses and intestinal morphology play an important role in increasing growth performance, nutrient absorption and disease resistance in fish, important outcomes in such a competitive and developing aquaculture sector.